« Spirit of the dead, rise up! […] and claim your story ». Représentation de l’esclavage et esthétique de la résistance dans Sankofa (Haile Gerima, 1993) - Claire Dutriaux (Transatlantica)
Haile Gerima, an independent Ethiopian filmmaker who belonged to the LA Rebellion film movement, directed films which dealt with various aspects of the African American and black diasporic experience. Sankofa (1993) was his first important critical and commercial success. The film used Akan mythology—in particular the sankofa bird symbolizing the need for every person to turn to the past in order to face their future—to broach the issue of resistance to oppression. In Sankofa, Gerima developed a politics and aesthetic of resistance. While the film’s political, ideological, and historical dimensions have been extensively analyzed, this essay focuses on its aesthetic dimension, which is the cornerstone of its ideological discourse on resistance to slavery.